Relationship between Mathematics education philosophy and traditional Malay culture in Serampang 12 - Nina Fadilah; Izwita Dewi; Faiz Ahyaningsih (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Philosophy requires humans to think intelligently to develop towards the next thought of knowledge. The presence of ethnomathematics is not a new thing but has existed since the introduction of mathematics itself as a form of advanced knowledge thinking related to mathematics learning. Through the concept of ethnomathematics, cultural practices can be studied so that students will better understand how their culture is related to mathematics. This study uses a qualitative descriptive research method with a type of ethnographic research that analyzes the movement pattern of traditional Malay dance culture in Serampang 12. The results of the research findings are in the form of variations in mathematics learning, in the form of media associated in the context of traditional Malay culture, so that students who have been considering boring and rigid learning can have a fun lesson because it is associate with the value of the beauty of a Traditional Dance who have a philosophy of politeness, order, togetherness or positive association. The exploration of movement patterns in the traditional dance of Serampang 12 also aims to make it easier for students to build a learning experience that connected to the visual and kinesthetic experience of students. AbstrakFilsafat menuntut manusia agar berpikir cerdas sehingga manusia tersebut dapat berkembang menuju pemikiran pengetahuan yang selanjutnya. Kehadiran etnomatematika bukan suatu hal yang baru melainkan sudah ada sejak diperkenalkan ilmu matematika itu sendiri sebagai bentuk pemikiran pengetahuan lanjutan terkait dengan pembelajaran matematika. Melalui konsep etnomatematika dapat dikaji praktik budaya sehingga peserta didik akan lebih memahami bagaimana budaya mereka terkait dengan matematika. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dengan jenis penelitian etnografi yang menganalisis pola gerakan budaya tari tradisional Melayu Serampang 12. Hasil temuan penelitian berupa variasi dalam pembelajaran matematika dimana media dikaitkan dalam konteks budaya tradisional Melayu, sehingga peserta didik yang selama ini menganggap pembelajaran membosankan dan kaku bisa menjadi pelajaran yang menyenangkan karena bisa dihubungkan dengan nilai keindahan suatu tarian tradisional serampang 12 yang memiliki filosofi kesopanan, keteraturan, kebersamaan atau pergaulan yang positif. Eksplorasi pola gerakan pada tarian tradisional Serampang 12 juga bertujuan untuk memberikan kemudahan peserta didik dalam membangun pengalaman belajar yang terhubung dengan pengalaman visual dan kinestetik peserta didik.Kata Kunci: budaya; filsafat; Matematika; pendidikan Matematika